2020
DOI: 10.3390/app10144825
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of Liquid Motion in a Flow-Based System on an Enzyme Aggregation State with an Atomic Force Microscopy Sensor: The Effect of Glycerol Flow

Abstract: Atomic force microscopy is employed to study the influence of the motion of a glycerol solution through a coiled (spiral-wound) polymeric communication pipe on the aggregation state of a protein, with the example of a horseradish peroxidase (HRP) enzyme. The measuring cell with the buffered solution of the protein was placed within the experimental setup over the pipe coil, through which glycerol was pumped. It is demonstrated that, in such a system, the flow of a non-aqueous liquid (glycerol) leads to a chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…This fact indicates that the flow-induced field only impacts the spatial structures of the protein globule near its surface, while not affecting its active site. The effects of HRP aggregation in the presence of electromagnetic fields were previously reported in our recent studies [ 8 , 35 , 36 ] and by Sun et al [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This fact indicates that the flow-induced field only impacts the spatial structures of the protein globule near its surface, while not affecting its active site. The effects of HRP aggregation in the presence of electromagnetic fields were previously reported in our recent studies [ 8 , 35 , 36 ] and by Sun et al [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 69%
“…The AFM experiments were carried out using the direct surface adsorption method [ 8 , 15 , 35 , 36 ], similar to [ 8 ]. Briefly, muscovite mica sheets (SPI, West Chester, PA, USA) were used as AFM substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that the incubation of a protein solution over the coiled pipe with flowing liquid leads to a change in adsorption properties of the protein macromolecules [5]. We discussed that the flow of a non-aqueous liquid (such as glycerol) generates an electric charge [5,6]. This charge induces an electric field, which, in turn, can affect proteins' properties.…”
Section: Introductionmentioning
confidence: 99%
“…The use of HRP protein in our experiments was justified in our previous papers [5,7,8]. Briefly, this protein was studied in much detail, and this is why it is often employed as a model in studies of enzymes, including peroxidases which play important roles in living systems [9].…”
Section: Introductionmentioning
confidence: 99%